PERENCANAAN PAJAK PENGHASILAN PADA PT SURYA PATRIOT MANDALA DI BADUNG - I Kadek Adhi Prmana; I. I. D. A. Manik Sastri; L.G. P. Sri Ekajayanti (KRISNA: Kumpulan Riset Akuntansi, 2019)
This research aims is to analyze income tax planning article 21 and income tax article 23, and provide options for the type of tax planning that can be applied to PT Surya Patriot Mandala so that the tax burden owed is more efficient. This research was conducted by interview, observation, and documentation using data obtained from PT Surya Patriot Mandala. The data analysis technique used is descriptive comparative that is describing or describing the data that has been collected without intending to provide conclusions that apply in general. The results of the study show that the gross up method of income tax article 21 can streamline payment of corporate income tax in the amount of Rp. 5,402,378 and income tax article 25 to be paid also decreased by Rp. 450,198, because the income tax article 21 provided by the company can be financed. In income tax article 23 the use of gross up method on transaction value can make PT Surya Patriot Mandala receive its income in a net manner. The tax base is based on a circular letter from the Director General of Taxes No. 05 / PJ.53 / 2003 and SE-53 / PJ / 2009 are treatments that can be chosen by PT Surya Patriot Mandala as a company providing labor services, but must be adapted to the circumstances and company policies. Tax clauses in work contracts, documents related to transactions, and incoming cash flows affect the tax treatment.